2010
DOI: 10.2209/tdcpublication.51.129
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stretching Stress on Gene Transcription Related to Early-phase Differentiation in Rat Periodontal Ligament Cells

Abstract: Mechanical stress such as occlusal and orthodontic loading has been suggested to induce a homeostatic and regenerative response in periodontal ligament (PDL), but the underlying mechanism remains to be clarified. The purpose of this study was to investigate expression of mRNAs encoding proteins involved in osteogenesis and homeostasis by PDL cells following application of tensile stress and characterize the relationship between such expression and the regenerative and homeostatic functions of the PDL. PDL cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Mechanical loading is also demonstrated to cause similar response. It has been demonstrated that stretching could induce Heat-Shock Proteins (HSPs) upregulation in endothelial cells [13], melanocytes [14], bladder smooth muscle cells [15], vascular smooth muscle cells [16], periodontal ligament cells [17], trabecular meshwork cells [18] and tendon fibroblast [19]. Similar to the IVD, the articular cartilage is also subjected to considerable compressive loading.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical loading is also demonstrated to cause similar response. It has been demonstrated that stretching could induce Heat-Shock Proteins (HSPs) upregulation in endothelial cells [13], melanocytes [14], bladder smooth muscle cells [15], vascular smooth muscle cells [16], periodontal ligament cells [17], trabecular meshwork cells [18] and tendon fibroblast [19]. Similar to the IVD, the articular cartilage is also subjected to considerable compressive loading.…”
Section: Introductionmentioning
confidence: 99%
“…In agreement with our results, in one of these studies, BMP-2 was increased by mechanical stimulation, and in another one, by PGE 2 -mediated inflammation [ 12 , 62 ]. Stretch-induced BMP-4, alike BMP-2, was also observed in tendon cells [ 64 ]; however, to our knowledge, no study has demonstrated its osteogenic potential in these cells. Altogether, a local increase in BMPs might modify the mineralizing capacity of entheseal cells to favor ossification in SpA joint.…”
Section: Discussionmentioning
confidence: 99%
“…Osterix is one of the key factors playing during the osteoblastic cell differentiation just down stream of Runx2, which regulate pre, immature-osteoblasts to matured osteoblast [18][19][20] . At present, some experimental data have been published regarding the gene expression profile of osteoblastic cell differentiation-related factors using IHC [21][22][23][24][25][26][27][28] , but the examination model is limited to in vitro using cultured cells.…”
Section: Discussionmentioning
confidence: 99%